2020
DOI: 10.3390/land9060198
|View full text |Cite
|
Sign up to set email alerts
|

Glacial Rock Flour as Soil Amendment in Subarctic Farming in South Greenland

Abstract: Agriculture in subarctic regions is limited by a short and cold growing season. With warming in the region, the number of growing days and, consequently, the potential for agricultural intensification and expansion may increase. However, subarctic soils are typically acidic, low in plant-available nutrients, and coarsely textured, so they require soil amendment prior to intensification. This is the case in South Greenland, where we tested the use of glacial rock flour (GRF) produced by glaciers as a soil amend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…This Fe source is particularly relevant to fjords and coastal regions surrounding the Greenland Ice Sheet (GrIS), which discharges ~1200 Gt of freshwater annually to surrounding waters (Bamber et al, 2018). The meltwater discharged from the GrIS can contain substantial loads (>3000 mg/L) of fine-grained glacially abraded particles that are rich in Fe and other biologically relevant elements including silicon (Si) (Meire et al, 2016;Sukstorf et al, 2020). Due to unabated warming Arctic air temperatures and intensified GrIS melting, fluxes of any glacially-derived elements that scale with discharge volume are expected to increase in the future (Vizcaíno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This Fe source is particularly relevant to fjords and coastal regions surrounding the Greenland Ice Sheet (GrIS), which discharges ~1200 Gt of freshwater annually to surrounding waters (Bamber et al, 2018). The meltwater discharged from the GrIS can contain substantial loads (>3000 mg/L) of fine-grained glacially abraded particles that are rich in Fe and other biologically relevant elements including silicon (Si) (Meire et al, 2016;Sukstorf et al, 2020). Due to unabated warming Arctic air temperatures and intensified GrIS melting, fluxes of any glacially-derived elements that scale with discharge volume are expected to increase in the future (Vizcaíno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the slow dissolution rates of the primary silicates found in the GRF, especially in cold environments, the results of Sukstorf et al. (2020) were expected. In contrast to conventional soil amendments, for example, organic and artificial fertilizers, or liming, the addition of a fine‐grained mineral material to soil is a long‐term and profound intervention on the soil, and any negative effect on the latter needs to be assessed before large‐scale application.…”
Section: Introductionmentioning
confidence: 75%
“…Furthermore, Gunnarsen (2020) concluded that high rates of GRF application increased biomass production in active soil environments following enhanced weathering of the mineral material. Sukstorf et al (2020) presented the results of a oneseason (2 mo) field experiment in Greenland and concluded that an amendment with only GRF was not suited as shortterm fertilizer; however, a combination of GRF and artificial N-P-K fertilizer significantly increased the yields. Regarding the slow dissolution rates of the primary silicates found in the GRF, especially in cold environments, the results of Sukstorf et al (2020) were expected.…”
Section: Core Ideasmentioning
confidence: 99%
See 2 more Smart Citations